ANALISIS PENYEBAB KERUSAKAN LORI PADA STASIUN STERILIZER DAN USULAN PERBAIKAN MENGGUNAKAN METODE DESKRIPTIF KUANTITATIF DI PABRIK ABC - Fauzan, Rifki; Silaban, Alvonco; Wahyuni, Sri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The trolley is a critical component in transporting Fresh Fruit Bunches (FFB) during the sterilization process in palm oil mills. Wheel damage often disrupts production. This study aims to identify the types of wheel damage, analyze their causes, and calculate the resulting downtime at PT ABC. The research employed field observations, interviews, and operational data analysis. Results indicate that the most common damages are flange wear and bearing failure due to excessive loads and insufficient lubrication, reducing daily production efficiency. Recommended mitigation measures include enhanced preventive maintenance schedules and standardization of trolley load to extend wheel lifespan.